Ratifikasi United Nations Convention Against Illicit Traffic in Narcotic and Psychotropic Substances 1988 Terhadap Pemberantasan Peredaran Gelap Narkotika di Indonesia - Anisa Aulia; Danial Danial; Mas Nana Juemena (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
Narcotics are substances or drugs that are natural, synthetic, or semi-synthetic which cause a decrease in consciousness, hallucinations, and excitability, and can cause dependence if misused. The problem is: How is the implementation of the United Nations Convention Against Illicit Traffic in Narcotic Drugs and Psychotropic Substances, 1988 towards eradicating illicit narcotics trafficking in Indonesia? The author uses transformation theory, legal certainty theory, and law enforcement theory in this thesis. The research specification in this thesis is descriptive analytical. The method used in this study is an empirical juridical method which is supported by a normative juridical method. The empirical juridical method is a research method carried out by researching directly into the field, while the normative juridical method is a research conducted by examining secondary materials. The data collection technique used is through interviews, which are supported by literature studies. The result of this study is: Indonesia has implemented the United Nations Convention Against Illicit Traffic In Narcotic Drugs and Psychotropic Substances, 1988 by ratifying the convention with Law Number 7 of 1997 as implementing legislation, as well as forming a law on narcotics, namely Law No. 22 of 1997 which was repealed by Law No. 35 of 2009.